Structural and functional characterization of a cold-adapted stand-alone TPM domain reveals a relationship between dynamics and phosphatase activity - Pellizza, L; Smal, C; Ithurralde, RE; Turjanski, AG; CICERO, DANIEL OSCAR (The FEBS Journal, 2016)
The TPM domain constitutes a family of recently characterized protein domains that are present in most living organisms. Although some progress has been made in understanding the cellular role of TPM-containing proteins, the relationship between structure and function is not clear yet. We have recently solved the solution and crystal structure of one TPM domain (BA42) from the Antarctic bacterium Bizionia argentinensis. In this work, we demonstrate that BA42 has phosphoric-monoester hydrolase activity. The activity of BA42 is strictly dependent on the binding of divalent metals and retains nearly 70% of the maximum at 4 °C, a typical characteristic of cold-adapted enzymes. From HSQC, 15N relaxation measurements, and molecular dynamics studies, we determine that the flexibility of the crossing loops was associated to the protein activity. Thermal unfolding experiments showed that the local increment in flexibility of Mg2+-bound BA42, when compared with Ca2+-bound BA42, is associated to a decrease in global protein stability. Finally, through mutagenesis experiments, we unambiguously demonstrate that the region comprising the metal-binding site participates in the catalytic mechanism. The results shown here contribute to the understanding of the relationship between structure and function of this new family of TPM domains providing important cues on the regulatory role of Mg2+ and Ca2+ and the molecular mechanism underlying enzyme activity at low temperatures.